The Management of difficult intubation in children - WALKER, ROBERT W.M.; ELLWOOD, JAMES (Pediatric anesthesia, 2009)
Summary This article looks at the current techniques and equipment recommended for the management of the difficult intubation scenario in pediatric practice. We discuss the general considerations including preoperative preparation, the preferred anesthetic technique and the use of both rigid laryngoscopic and fiberoptic techniques for intubation. The unanticipated scenario is also discussed.